Pravacanasāra - Kundakunda; Sahajānanda Sarasvatī, Swami, 1889-1950.; Amr̥tacandra, active 10th century (Meraṭha : Sahajānanda Śāstramālā, 1979)
Prakrit treatise, with Tattvadīpikā Sanskrit commentary and Saptadaśāṅgī supercommentary, on salvation according to Jainism.
Hindi, Prakrit, and Sanskrit.
Mode of access: Internet.
Keywords: Salvation -- Jainism -- Early works to 1800.